Sustainable Development Goals (SDGs): Progress and Challenges in Emerging Markets - Ibrahim, Fifi Nurafifah; Ikhtiari, Kirana; Syam, Hasnidar; Nurfadila, Nurfadila; Abna, Nurul Rafiqa Auliyah; Susanto, Ari (Journal of Economics Review (JOER), 2024)
This study explores the implementation of Sustainable Development Goals (SDGs) in emerging markets, focusing on progress, challenges, and pathways for improvement. Drawing on a literature review and empirical evidence, the research investigates the current status of SDG advancement, identifying key obstacles such as socio-economic disparities, institutional complexities, and infrastructure deficits. Findings reveal significant progress in integrating SDGs into national agendas yet underscore persistent challenges hindering further advancement. The study emphasizes the need for tailored, adaptive strategies to address contextual complexities and promote inclusivity. Implications suggest the importance of collaborative endeavors among stakeholders to overcome barriers and foster sustainable development. By addressing these challenges collectively, emerging markets can realize their full potential in driving inclusive and resilient societies aligned with SDG principles.